Improving Students’ Writing Ability of Descriptive Paragraph and Their Creativity through Picture Word Inductive Model (PWIM) at Second Semester of Non-English Department Students UIN Raden Fatah Palembang - Elsa Ninda Meifira; Hermawati Syarif (International Journal of Educational Dynamics, 2020)
This study aimed to find out the improvement of students’ writing ability of descriptive paragraph through PWIM at second semester of non-English department students in UIN Raden Fatah Palembang. The type of this research was classroom action reseacrh which were conducted in two cycles. Every cycle consisted of five meetings; four meetings to do treatments, one meeting for test. The participations were the second semester of Hadith Science students that consisted of 37 students. This research was analyzed by quantitative data; namely, writing tasks and writing tests. The result from cycle I to cycle II showed that PWIM improved students’ writing ability of descriptive paragraph and increased their creativity in writing that could be seen from the activeness and participation of students in the learning process.